Toxic Blue-Green Algal Blooms in Keban Dam Lake and Lake Hazar - Şen, Bülent; Sönmez, Feray (My University, 2024)
The blue-green algae are main members of summer phytoplankton in Keban Dam Lake and to some extent in Lake Hazar. Sporadic occurrences of Microcystis aeruginosa blooms were noticable in Keban Dam Lake whilst blooms of Nodularia spumigena was characteristic in Lake Hazar. Three variants of cyanotoxin namely microcystin-RR, microcystin-YR and microcystin-LR were analyzed in Keban Dam Lake only during M.aeruginosa blooms. Their concentrations were determined in the range of microcystin-RR 0.27-1.12 µg L-1; microcystin-YR 0.12-0.54 µg/L and microcystin-LR 0.27-1.15 µg/L respectively. Chlorophyll a concentrations were found to range 16-20 µg L-1 and 32-36 µg L-1 during two blooms of M. aeruginosa. Nodularia spumigena appeared in the first week of june (2010) with a biomass of 1.368 mg L-1 and it proliferated rapidly giving rise to a bloom within two weeks in Hazar Lake. The bloom lasted nearly four weeks and maximum biomass was recorded as 28.4 mgL-1. Chlorophyll a concentration was found to be 12-14 µg L-1 in the first two weeks of the active multiplication period and increased up to 21-24 µg L-1 at the maximum bloom level. Nodularin (toxin of N. spumigena) was detected in the samples with concentrations varied between 42.3 and 607 µgL-1.
Keywords: Microcystis aeruginosa; Keban Dam Lake; Lake Hazar; Toxic algal blooms; Nodularia spumigena